The efficiency of multimedia technologies in the process of a foreign language teaching to non-linguistic students - Iulia Yurievna Kotliarenko; Elena Alexandrovna Nikolaeva (Вестник Майкопского государственного технологического университета)
The relevance of the research is due to the process of active implementation of multimedia technologies in the learning process. However, the possibilities and didactic potential of multimedia technologies are often exaggerated. Therefore, the purpose of the research is to systematize the effects of the multimedia introduction process and formulate the conditions for the effective use of these technologies in the framework of a foreign language course for students of non-linguistic specialties.The following methods of theoretical analysis have been used in the research: axiomatic, deduction, analysis and synthesis.The results of the research have shown that multimedia makes it possible to adapt the educational process to the student's cognitive patterns, constructively influence his/her emotional background and motivation for learning. The negative effects of using multimedia are associated with a high level of cognitive load in a student, distraction of attention, a shift in attention from the content of the studied material to its form, and, as a result, the lack of consistency in the perception of information. The objective reasons for the decrease in the level of effectiveness of multimedia technologies include: their natural limitations in solving didactic problems, technical support for the implementation of multimedia courses, the level of competence of teachers in the use of these technologies.As a result of the research, the authors have concluded that the pedagogical design of the course based on the cognitive theory of multimedia learning and the taxonomy of pedagogical goals should become the basis for making decisions about the amount of use and quality requirements of multimedia technologies.